Reversibility : politics under conditions of uncertainty - Behr, Hartmut (McGill-Queen's University Press, 2024)
"Western modernity is characterized by instrumental relations between humans and nature, as well as between humans themselves, that have caused irreversible environmental and social exploitation and degradation. Many policy documents, such as those by the United Nations Environment Programme, warn of the uncertainty and unpredictability of our precarious conditions due to our social and ecological interrelations and interdependencies. Accepting that our position in the world does not allow us secure knowledge of the consequences of politics, Reversibility - Politics under Conditions of Uncertainty asks how we can act politically in a responsible way when we cannot predict the outcomes of our decisions. Hartmut Behr diagnoses Western modernity and its manifold crises as dominated by the view that fellow humans and natural environments are merely means to our individual ends. Behr introduces a novel ethics of self-restraint and the principle of reversibility - a commitment to political actions whose effects shall not be indefinite or immutable - to build a policy framework that demands both ethical and practical reflection on the conditions of action and that accounts for the limitations under which we act and live. Identifying an urgent need for re-thinking political progress and for policy reform, Reversibility - Politics under Conditions of Uncertainty presents a new understanding of the self and of political responsibility centred in a genuine acknowledgment of the human condition."-- Provided by publisher.
Keywords: Political science -- Philosophy.; Political ethics.; Contingency (Philosophy); Uncertainty.; Morale politique.; Contingence (Philosophie); Incertitude.; PHILOSOPHY / Political